Barriers to Engagement in Apprenticeship Programme Identifying Role of State, Employer and Apprentices through Study of Delhi (Global Journal of Management and Business Research, 2020)
This study critically examines apprenticeship system in India with case study of Delhi Sound apprenticeship system is desirable for transferring people smoothly from world of learning to world of work For a country with 485 million workforce a miniscule number of apprentices i e around 3 lakhs get trained every year Total establishments registered on apprenticeship portal are 67650 all over India Stipend given to the apprentices is so less that they don t want to enter into industries as apprentices Even the fixed stipend rules are not followed due to lack of accountability of the firms Private firms as found in numerous studies don t comply with legislative requirements while apprentices view their training period as avenue for future employment rather than as a mode of training and all this affects quality of training There is a need of a more comprehensive labour market information system which can be of benefit to all 3 key stakeholders- employers job-seekers and government Strong apprenticeship paradigm requires cooperation of industrial associations government and participating companies it cannot be bought off the market but is in need of nurturing at the shop floor This study recommends reforms that Delhi can do to improve the apprenticeship conditions